Inspiring global classroom session on effective communication in meetings - Siti Ainun Jariyah, Hassan; Hamizah, Zahari (UMPSA, 2025)
PEKAN, 13 June 2025 – The Centre for Modern Languages (CML) continues to enhance global academic engagement through Global Classroom initiatives, this time focusing on the topic, “Effective Language Skills in Professional Meetings”, a topic that is highly relevant in today’s global and professional settings. The Global Classroom session was organised for students enrolled in the ULE2342 (Degree) and ULE2232 (Diploma), English for Professional Communication course.